Float analysis : - Woods, Steve (J. Wiley & Sons, 2002)
his comprehensive trading guide also covers: *Ten breakthrough discoveries that will change the way you analyze stock charts *Support and resistance redefined *Successful trading strategies *How to understand and profit from indicators *How Gann Theory inspired float analysis